A new furofuran lignan from Piper terminaliflorum Tseng. Issue 3 (1st February 2018) - Liu, Tie; Liang, Qian; Zhang, Xin-Min; Huang, Shen-Yang; Xu, Wen-Hui
Abstract: The chemical investigation of whole plants Piper terminaliflorum Tseng led to the isolation of one new furofuran lignan, 7-methoxyasarinin (1 ), along with three known amide alkaloids (2 –4 ) as N -3, 5-dimethoxy-4-hydroxycinnamoylpyrrole (2 ), dihydropipercide (3 ) and 1-[(2 E, 4 E, 9 E )-10-(3, 4-Methylenedioxyphenyl)-2, 4, 9-undecatrienoyl]pyrrolidine (4 ). Their structures were elucidated by extensive spectroscopic analyses, including 1D, 2D NMR and HR-ESI-MS, and by comparison with the literature. Compounds (2 –4 ) were isolated from Piper terminaliflorum Tseng for the first time. All isolated compounds (1 –4 ) were evaluated for their cytotoxic activities against five human cancer cell lines (including A-549, SMMC-7721, HL-60, MCF-7 and SW-480). Abstract :